Amyloid-beta peptide and phosphorylated tau in the frontopolar cerebral cortex and in the cerebellum of toothed whales: aging versus hypoxia - Sacchini, Simona; Diaz Delgado, Josue; Espinosa De Los Monteros Y Zayas, Antonio; Paz Sanchez, Yania; Bernaldo De Quirós Miranda, Yara; Sierra Pulpillo, Eva María; Arbelo Hernández, Manuel Antonio; Herráez Thomas, Pedro Manuel; Fernández Rodríguez, Antonio Jesús (Biology Open, 2020)
Hypoxia could be a possible risk factor for neurodegenerative alterations in cetaceans’ brain. Among toothed whales, the beaked whales are particularly cryptic and routinely dive deeper than 1000 m for about 1 h in order to hunt squids and fishes. Samples of frontal cerebral and cerebellar cortex were collected from nine animals, representing six different species of the suborder Odontoceti. Immunohistochemical analysis employed anti-β-amyloid (Aβ) and anti-neurofibrillary tangle (NFT) antibodies. Six of nine (67%) animals showed positive immunolabeling for Aβ and/or NFT. The most striking findings were intranuclear Aβ immunopositivity in cerebral cortical neurons and NFT immunopositivity in cerebellar Purkinje neurons with granulovacuolar degeneration. Aβ plaques were also observed in one elderly animal. Herein, we present immunohistopathological findings classic of Alzheimer's and other neurodegenerative diseases in humans. Our findings could be linked to hypoxic phenomena, as they were more extensive in beaked whales. Despite their adaptations, cetaceans could be vulnerable to sustained and repetitive brain hypoxia. 0,936 2,422 Q1 Q2 SCIE